2021
DOI: 10.1021/acsomega.0c06227
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Quantum Dots Embedded in Silica Matrices Made by Flame Spray Pyrolysis

Abstract: Quantum dots have unique size-dependent properties and promising applications. However, their use in many applications remains hindered by mechanical, thermal, and chemical instability and the lack of viable quantum dot mass-production processes. Embedding quantum dots in matrices such as silica counteracts the instability challenges in some applications while preserving their unique properties and applicability. Here, we synthesize quantum dots of four different metal oxides embedded in a silica matrix in a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
(96 reference statements)
1
13
0
Order By: Relevance
“…16 Then, we have shown that the flame spray pyrolysis (FSP) process, a mass-production nanoparticle synthesis technology, can synthesize metal oxide quantum dots with any bandgap energy from the UVC to the dark red region of the light spectrum. 17 Finally, we have shown that flame-made titania contains a significant TiO 2 (B) crystalline fraction and is 2-3 times more efficient in catalyzing epoxy photo-polymerization than P25 titania, 18 the gold standard 19 for photocatalysis.…”
Section: Introductionmentioning
confidence: 97%
“…16 Then, we have shown that the flame spray pyrolysis (FSP) process, a mass-production nanoparticle synthesis technology, can synthesize metal oxide quantum dots with any bandgap energy from the UVC to the dark red region of the light spectrum. 17 Finally, we have shown that flame-made titania contains a significant TiO 2 (B) crystalline fraction and is 2-3 times more efficient in catalyzing epoxy photo-polymerization than P25 titania, 18 the gold standard 19 for photocatalysis.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, quantum dots have properties intermediate between bulk materials and discrete atoms or molecules. They can be formed from various materials such as metal atoms, [23,24] metal oxides, [25,26] metal sulfides, [27][28][29] or carbon materials. [30][31][32] Their size gives them special features that facilitate a wide variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…For two-dimensional (2D) materials that are susceptible to exfoliation [15], such as graphene [16] and black phosphorous (BP) [17], the QDs are often obtained with mechanical or chemical exfoliation methods. Metal oxide QDs also show wide applications such as photocatalysis (TiO 2 ), ultraviolet protection films (ZnO), gas sensing (SnO 2 ), and high-temperature superconductors (CuO) [18]. However, due to their high surface energy, they have heightened mechanical, thermal, and chemical instability.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore relatively difficult to achieve viable large-scale production. Embedding them in amorphous matrices [18] has been reported to be an effective way to obtain stable metal oxide QDs. Analogously, embedding them in a crystal matrix would be worth trying.…”
Section: Introductionmentioning
confidence: 99%